Gestão de pessoas por competências: um estudo de caso em organização do setor industrial de Sobral/CE - Pompeu, Carlena Gurgel (2014)
This research has as main goal identify, according the perception of leaders and not leaders, the major changes happened in people management with the implementation of competency management in organization of the industrial sector from Sobral-CE. The relevance of this study is to verify the presence or not of improvements in overall results this company in terms of development actions more integrated; more strategic corporate action by its employees, as to achieve strategic results; greater focus on developing and enhancement of employees; alignment between people's expectations and the company, increased efficiency in relation to market pressures, etc. This part study, essentially, of the assumptions of which the management of people in industrial organization associated with the management by skills improves quality and results of the recruitment and selection of the organization, that the management of people in industrial organization associated with management by skills improves the quality and the results of training process and organization development , and that the management of people in industrial organization associated with the management by skills improves quality and outcomes of positions , careers and salaries of the organization. Was realized to the theoretical basement a survey about people management, strategic management by people and management by skills. In methodology is presented the case study as a research method, where the data collection occurred through the application of individual interviews semi-structured, in which were used two roadmaps and two forms for registration the data of the interviews, and how analysis data technique was used the content analysis, and the software NVivo 10 for analysis the data. Constitute subjects of this research the manager of Human Resources and 27 employees of the respective company. The research findings indicate that management by skills provided changes in the sub- process of people management, making them more strategic and aligned, besides having generated a lot of improvement on the overall performance of the company.